Sistem Pakar Rekomendasi Produk Asuransi Jiwa Berdasarkan Profil Nasabah menggunakan Algoritma Forward Chaining - Istiqomah, Nalar; Novika, Fanny (Premium Insurance Business Journal, 2024)
The aim of this research is to build a web-based expert system that can provide life insurance product recommendations. This expert system can be used to help people choose life insurance products that suit their own profile. This research began by conducting a literature study to determine the type of life insurance product and compiling a questionnaire which would later be given to experts. The results of this questionnaire are used as the basis for expert system knowledge which will later be processed using a forward chaining algorithm. From this process, 6 rules were obtained that can be used to recommend life insurance products. After the rules are obtained, a web based expert system is built using the PHP programming language. The expert system was tested using the black box method. From the test results, it is known that the system can carry out its functions well. Therefore, the website can be published on the internet and can be accessed at consurence.id.